Analysis of an Electrochemical Filter for Removing Carbon Monoxide from Reformate Hydrogen. Issue 10 (1st January 2015) - Balasubramanian, Sivagaminathan; Weidner, John W.
Abstract : We studied the operation of a twin-cell electrochemical filter for removing carbon monoxide (CO) from reformate hydrogen by periodically adsorbing and then electrochemically oxidizing CO on the electrode. During the adsorption step, we studied the effects of feed CO concentration, flow rate, electrode catalyst loading, type of feeder gas, and temperature on CO breakthrough. We then applied a fixed bed adsorber model to show that the breakthrough time could be accurately correlated to the adsorption-step operating parameters. Since the oxidation step was found to be much faster than that for CO breakthrough, adsorption time should dictate switching time. This insight was used to predict steady-state filter performance, and the prediction was validated for an electrochemical filter operated with CO contaminated hydrogen to decrease the CO concentration from 10, 000 to 10 ppm. The model was also used to explore the employability of an electrochemical filter over a range of operating conditions by considering the comparative electrode area of a filter with that of a fuel cell.